2021
DOI: 10.3126/kumj.v19i1.49549
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ejection Fraction in Patients undergoing Coronary Artery Bypass Grafting with Impaired Left Ventricular Function

Abstract: Background Myocardial revascularization surgery has shown better long term survival expectancy compared to medical therapy in patient with impaired left ventricular function. Objective To evaluate the change in ejection fraction after 90 days in patients who underwent coronary artery bypass surgery and had preoperative left ventricular ejection fraction of less than and equal to 45% in a single cardiac center of Nepal over the period of 2 years. Method Out of 82 eligible patients during 2 years, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…K.B. Rana et al [19] found in their prospective study of 200 patients undergoing CABG a relation between pre-operative left ventricular dysfunction and LCOS after surgery, which was significantly different in patients with pre-operative ejection fraction < 40%, compared to ejection fraction ≥ 40%. P. Amabili et al [20] used the systolic global longitudinal strain to evaluate left ventricular function and determine that GLS was a significant risk factor for LCOS after cardiac surgery, while analysis of myocardial strain appears to improve the prediction of LCOS.…”
Section: Table 8 Risk Factors For Lcosmentioning
confidence: 97%
“…K.B. Rana et al [19] found in their prospective study of 200 patients undergoing CABG a relation between pre-operative left ventricular dysfunction and LCOS after surgery, which was significantly different in patients with pre-operative ejection fraction < 40%, compared to ejection fraction ≥ 40%. P. Amabili et al [20] used the systolic global longitudinal strain to evaluate left ventricular function and determine that GLS was a significant risk factor for LCOS after cardiac surgery, while analysis of myocardial strain appears to improve the prediction of LCOS.…”
Section: Table 8 Risk Factors For Lcosmentioning
confidence: 97%